2002
DOI: 10.1023/a:1016046810103
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The influence of clofibrate on the stereoconversion of fenoprofen (FPF) was studied in guinea pigs. This hypolipidaemic agent has been related to some biochemical changes in the liver leading to an increase in the chiral inversion process. Two groups of animals (n = 6 per group) were pretreated with oral doses of clofibrate (280 mg/kg per day) for three days and were then given (R)- or (S)-FPF (5 mg/kg, IV). The FPF enantiomers were extracted from the guinea-pigs' plasma using a solid phase procedure and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Ibuprofen is extensively metabolized via the oxidation and glucuronidation routes showing selectivity for (+)-(S)-ibuprofen. In addition, unidirectional inversion of the (−)-(R)-to (+)-(S)-enantiomer also occurs in vivo [2,[4][5][6]. As a consequence, plasma concentrations of (−)-(R)-and (+)-(S)-ibuprofen differ significantly, resulting in stereoselective pharmacokinetic parameters [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ibuprofen is extensively metabolized via the oxidation and glucuronidation routes showing selectivity for (+)-(S)-ibuprofen. In addition, unidirectional inversion of the (−)-(R)-to (+)-(S)-enantiomer also occurs in vivo [2,[4][5][6]. As a consequence, plasma concentrations of (−)-(R)-and (+)-(S)-ibuprofen differ significantly, resulting in stereoselective pharmacokinetic parameters [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previously studies indicated that the effect on cyclo-oxygenase of fenoprofen and ketoprofen were resulted from the S-(+) enantiomer [28,29]. Among them, the metabolic chiral inversion process corresponds to a selective unidirectional transformation from the inactive R-(−) to the active S-(+) enantiomer [30,31]. Therefore, we may presume that with the incubation time expanding, the possible metabolic chiral transformation inverses and exacerbates the stereoselective glucuronidation of ZPF in rat liver microsomes.…”
Section: Concentration Spiked (M)mentioning
confidence: 99%
“…In various animal species and human beings, ibuprofen has been studied widely with unidirectional chiral inversion [35, 67-69, 75, 76-83]. The unidirectional chiral inversion of R-fenoprofen to its active antipode, with high interspecies variation in the inversion magnitude, was reported in rat [16,[84][85][86], guinea pig [86,87], cat [88], and humans [89,90]. In rats [91] and humans [92], benoxaprofen showed stereospecific inversion from R-to S-enantiomer with a higher inversion rate in rats than in humans.…”
Section: In Vivo Racemizationmentioning
confidence: 99%